KONSEKUENSI HUKUM DAN TANGGUNG JAWAB NOTARIS TERHADAP AKTA YANG MENGANDUNG UNSUR PENYALAHGUNAAN KEADAAN. - Syaputra, Maulana; Irhamsah, Irhamsah; Ridwan, Refki (SENTRI: Jurnal Riset Ilmiah, 2024)
The notary profession provides legal certainty and maintains legal enforceability in civil law jurisdictions. In the agreement, legal conditions must be met, and the Notary has authority in the civil sphere. Abuse of circumstances can lead to the cancellation of the agreement, and the Precautionary Principle of Notaries prevents it with the practice of identity recognition, data verification, and fulfillment of technical conditions. Although the abuse of circumstances is not directly regulated, the notary must guarantee the correctness of the deed in accordance with the law. This study raises the issue of how the legal consequences of the authentic deed made before the notary in which one party abuses the circumstances and how the responsibility of the notary to the deed made where one party abuses the circumstances of the other party, using the theory of legal consequences and responsibility theory. The method used in this study is the normative juridical method, namely legal research conducted by researching library materials or secondary data only. The research approach used is the approach of legislation, case approach, analytical approach and conceptual approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, researching library materials (books, scientific journals, research reports) and other sources of legal materials that are relevant to the legal issues under study. For technical analysis of legal material is done by systematic and grammatical interpretation. The result of this study is that the authentic deed made before a notary, if it is in accordance with the legislation, remains valid and binding on the parties. However, if there is an indication of abuse of circumstances by one of the parties, the court can cancel it, provided that it can be proven in a judicial process and the Notary has the responsibility to make the authentic deed honestly and with full precision, according to the legislation. If one of the parties misuses the circumstances and the court invalidates the deed, the notary can be held accountable or demand compensation, provided that it is proven that there was an unlawful act in the creation of the authentic deed.